2008
DOI: 10.1016/j.msea.2007.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Global mechanical tensioning for the management of residual stresses in welds

Abstract: The general principles behind the global mechanical tensioning technique for controlling weld residual stresses are examined using a finite element model to follow their evolution throughout the welding process. While we focus specifically on friction stir welding, the tool is represented simply as a heat source. As a result, the findings have relevance to a wide range of welding processes. For aluminium alloy friction stir welds, the maximum longitudinal weld stresses have been reported to fall approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 28 publications
5
74
0
Order By: Relevance
“…The power was distributed in each case in proportion to the surface velocity. For the probe, the shoulder power was increased in proportion to the radius across the ring source surface (as described by Richards et al, 2008). Standard values of thermal conductivity were used for the AA7050 alloy plate.…”
Section: Modellingmentioning
confidence: 99%
“…The power was distributed in each case in proportion to the surface velocity. For the probe, the shoulder power was increased in proportion to the radius across the ring source surface (as described by Richards et al, 2008). Standard values of thermal conductivity were used for the AA7050 alloy plate.…”
Section: Modellingmentioning
confidence: 99%
“…However, the actual magnitude depends on the thermal field and the properties of the material, specifically its straintemperature and yield stress-temperature relationships [12]. For example, in aluminium alloy welds the development of tensile stresses at the weld interface is normally limited by the low elevatedtemperature yield stress and low post-weld hardness compared with the parent metal (see Figure 3), resulting in a characteristic 'M-shaped' tensile stress profile [13,14]. However, in fusion welds the total size of the tensile region is typically larger than the extent of the melted zone (Figure 3), corresponding instead to the extent of plastic deformation induced by thermal stress.…”
Section: Formation Of Residual Stresses During Weldingmentioning
confidence: 99%
“…The mechanism by which this reduces the residual stress is summarised by Richards et al [13,119]. Essentially, the magnitude of the tensile longitudinal stress which can exist at the weld is always limited by the yield strength of the weld material.…”
Section: Global Mechanical Tensioningmentioning
confidence: 99%
“…These include post-weld heat treatment (Ref 6), shot peening, modification of the structural configurations, and the implementation of thermal tensioning techniques (Ref 7,8). It has also been reported that application of cold rolling is capable not only of removing the residual stress but depending on its magnitude it may also form beneficial compressive stress state .…”
Section: Introductionmentioning
confidence: 99%